Analisis Data Angin Permukaan di Bandara Udara Depati Amir Pangkalpinang Menggunakan Metode Windrose - Septika, Dea; Fatikasari, Annisa; Kusmita, Tri (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Pangkalpinang is a city in the Bangka Belitung Islands that is close to the sea. This indicates that Pangkalpinang is influenced by land winds and sea breezes. The purpose of this study is to analyse the percentage of wind speed and maximum wind speed in Pangkalpinang City in each month. The data used were obtained from synoptic observations of the Depati Amir Class I Meteorological Station in Pangkalpinang from January to December from 2011 to 2020. The data obtained is processed using WRPLOT (Wind Rose Plots for Meteorological Data) software to determine the direction and magnitude of wind speed and produce wind pattern images in the form of wind rose diagrams. The results obtained show that the dominant wind blows from the Southeast (112 - 157°) with the highest wind speed of 1 - 4 knots with a percentage of 42.9%, while the maximum wind speed throughout 2011 - 2020 is 28 knots which occurred in the period January - December 2013. The results obtained show that the wind conditions at Depati Amir Airport Pangkalpinang are still safe for aircraft take-off and landing operations.